2010
DOI: 10.4314/ajbr.v7i3.54185
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal contamination of <i>Clarias gariepinus</i> from a lake and fish farm in Ibadan, Nigeria

Abstract: Adult Clarias gariepinus (African Catfish)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
67
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(79 citation statements)
references
References 4 publications
10
67
0
Order By: Relevance
“…Among aquatic animals, fishes are widely used to evaluate the health of aquatic ecosystems because pollutants build up in the food chain and are responsible for adverse effects and consequent death [7,8]. In this study, the concentration of metals in fish (Catla catla and Labeo rohita) organs (liver gill and muscle) were used to calculate Bioaccumulation Factor (BAF).…”
Section: Introductionmentioning
confidence: 99%
“…Among aquatic animals, fishes are widely used to evaluate the health of aquatic ecosystems because pollutants build up in the food chain and are responsible for adverse effects and consequent death [7,8]. In this study, the concentration of metals in fish (Catla catla and Labeo rohita) organs (liver gill and muscle) were used to calculate Bioaccumulation Factor (BAF).…”
Section: Introductionmentioning
confidence: 99%
“…Owing to their toxicity and cumulative effect, discharge of heavy metals into the aquatic environments can alter the diversity of aquatic species and ecosystems (Berga, 2006). Aquatic organisms (such as fish and shell fish) accumulate heavy metals concentrations many times higher than what is present in water or sediment (Olaifa et al, 2004;George et al, 2013). At low concentration, some heavy metals such as iron, manganese, copper, *Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…Of the over 32,800 species of fishes, the African Catfish (Clarias gariepinus) is among the most popular in Nigeria's wild waters and aquaculture media (Amos and Bolorunduro, 2000), this is primarily due to their fast growth, hardiness, resistance to diseases, easy to breed both in captivity and wild. However, with these merits comes some drawbacks, as several studies have shown that wild captured fishes with potential of being hardy, bio-accumulate heavy metals to a large extent that has far-reaching health risks (Brown and Walls, 1997;Yilmaz, 2003;Hajeb et al, 2009;Olaifa et al, 2010;Mieiro et al, 2012;Bashir et al, 2013). With the growing awareness of eating healthy, there has been a rising consumption of both wild and farmed fish meat in Nigeria, this is in addition to the very low level of consumer safety control in place and inadequate pollution control measures in the nation's waters, inclusive of River Galma.…”
Section: Introductionmentioning
confidence: 99%